Development of Database System for Thepsatri Rajabhat University Archives - Rattanasermpong, Ph.D., Asst. Prof.Mayuri (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The purposes of this study were to 1) develop an archives database system and, 2) assess the efficiency of the archive database system of Thepsatri Rajabhat University. The collected data was analyzed and designed by the Aleph integrated library system program to develop database system. A sample consisted of a database specialist, a library system specialist, an archive specialist of Thepsatri Rajabhat University, a librarian who works in archival services, an information service librarian, and an information resource analysis librarian of the Office of Academic Resources and Information Technology of Thepsatri Rajabhat University, and 89 teachers, staff, and students. The instrument consisted of system efficiency assessment and user satisfaction questionnaire. Statistics consisted of percentage, mean and standard deviation. The findings showed that: 1. Developed a database system for archives documents of Thepsatri Rajabhat University, It was found that archival documents can be organized into categories according to the principles of classification. You can search by index, keyword, subject or title by typing commands. Supports multi-user access at the same time, flexible processing of adding, deleting, editing and retrieving data quickly including displaying it in the form of a bibliographic list. And 2. Assessing the efficiency of the archive database system showed that overall, it was appropriate and at a good level. There are 3 aspects that are sorted in descending order as follows: data security, system capability, and the accuracy of the operation system aspects. As for the service satisfaction of the users, it was found that the overall satisfaction level was at the high level. There are 3 aspects when sorted in descending order which are database accuracy, searching results, and the scope of the database aspects.